A Systematic Review of Healthcare Information Systems in the Medical Field - Balqis Nurmauli Damanik; Syahferi Anwar (International Forum of Researchers and Lecturers, 2025)
Healthcare Information Systems (HIS) play a critical role in modern medical services by improving patient data management, clinical decision-making, and overall healthcare efficiency. However, existing HIS models face challenges related to interoperability, security, and processing efficiency. This study conducts a systematic literature review to evaluate cloud-based, blockchain-enhanced, and AI-driven HIS solutions. The proposed hybrid HIS model integrates AI-driven decision-making with blockchain-based security to enhance accuracy, interoperability, and data protection. The evaluation metrics include accuracy, latency, and security score, comparing the proposed system with state-of-the-art HIS implementations. Experimental results indicate that the hybrid HIS model achieves 93.4% accuracy, a security score of 0.90, and reduced latency (220 ms), outperforming traditional cloud-based and standalone blockchain solutions. These findings demonstrate that a hybrid approach balances efficiency and security, making HIS more practical for real-world applications. Future research should focus on real-world deployment, computational cost reduction, and regulatory compliance.